TINJAUAN YURIDIS TERHADAP PELAKU TINDAK PIDANA PENADAHAN KENDARAAN BERMOTOR RODA DUA YANG TERJADI DI KOTA SAMARINDA - Arlini Arlini (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
AbstractArlini faculty of law university 17 august 1945 Samarinda, 2013 a juridical review of the perpetrators of two-wheeled motor vehicle crimes perpetrated in samarinda city. Under the quidence of Ony Rosifany SH.M.,Hum as mentor I and Drawan Hasyim, SH.Msi as lecturer II.The purpose of this study is to determine the factors causing the criminal act of two wheeled motorcycles that accurred in the city of Samarinda.  and the efforts undertaken by the city police in Samarinda.  countermeasures criminal fencing two-wheeled motor vehicle as well lega sanctions against perpetrators of two- wheeled motor vehicle raid.  That happened in Samarinda city. This research is done in the police resort Samarinda and the state court of Samarinda by taking relevant data and conducting interviews with related parties.  In addition the authors also conduct literature studies using various literature and legislation related to the problems discussed in this thesis.Besed on research in obtaining conclusion that is: (1) factors causing the occurrence of criminal act of two-wheeled motor vehicle that happened in Samarinda city that is. Because of the number of thefts, opportunity factors, economi factors. (2) efforts made by the police that is by means of preventive and repressive done by urge people to buy used motorcycles must be equipped with valid letters. (3) legal sanctions against the perpetrator that is in accor dance with existing laws and regulations article 480 of the criminal code.“premises of up to four years imprisonmend or a fine of up to Rp. 900,- (nine hundred rupiah)Because as a conspiracy, whoever buys rent, accepts exchange, accepts lien, accepts as a gift or because they want to make a profit sell, trade, mortgaging, carrying, storing, or hiding something that he knows or deserves in scribe obtained for a crime.Whoever profits frm the proceeds of any good the he knows or should have in his proof that the goods are acquired for a crime. KEYWORDS : fencing